2019
DOI: 10.3389/fneur.2019.00442
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Reorganization of the Brain in Migraine Without Aura

Abstract: It remains unknown whether migraine headache has a progressive component in its pathophysiology. Quantitative MRI may provide valuable insight into abnormal changes in the migraine interictum and assist in identifying disrupted brain networks. We carried out a data-driven study of structural integrity and functional connectivity of the resting brain in migraine without aura. MRI scanning was performed in 36 patients suffering from episodic migraine without aura and 33 age-matched healthy subjects. Voxel-wise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
3
25
2
Order By: Relevance
“…Though the role of the cerebellum (including crus I) in migraine is not well defined, it is known to exert an inhibitory control on cerebral cortex (Brighina et al, 2009 ; Moulton et al, 2010 ; Mehnert and May, 2019 ). The DMN is involved in several cognitive processes, such as memory, problem solving, and planning (Buckner et al, 2008 ; Lo Buono et al, 2017 ), as well as perception and processing of painful stimuli (Soheili-Nezhad et al, 2019 ). Specifically, the hippocampus and PHG are associated with learning and memory formation, as well as pain-related attention and anxiety (Buckner et al, 2008 ; Liu and Chen, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the role of the cerebellum (including crus I) in migraine is not well defined, it is known to exert an inhibitory control on cerebral cortex (Brighina et al, 2009 ; Moulton et al, 2010 ; Mehnert and May, 2019 ). The DMN is involved in several cognitive processes, such as memory, problem solving, and planning (Buckner et al, 2008 ; Lo Buono et al, 2017 ), as well as perception and processing of painful stimuli (Soheili-Nezhad et al, 2019 ). Specifically, the hippocampus and PHG are associated with learning and memory formation, as well as pain-related attention and anxiety (Buckner et al, 2008 ; Liu and Chen, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, findings across the resting-state MRI studies on migraine are complex and often inconsistent (Skorobogatykh et al, 2019 ). For example, while some researchers reported increased FC for the insula (Hadjikhani et al, 2013 ; Yuan et al, 2013 ) or the periaqueductal gray (Mainero et al, 2011 ) in patients with migraine, others reported decreased FC in these regions (Chen et al, 2017 ; Yu et al, 2017b ; Soheili-Nezhad et al, 2019 ). Furthermore, though reduced FC within the DMN and executive network has been repeatedly detected, negative or opposite results have also been observed in some migraine studies (Ellingson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence suggests atypical sensory processing in the cortex of migraine patients, especially in the somatosensory, visual, and olfactory-related areas [18,19]. The results of a study based on whole-head magnetoencephalography (MEG) showed aberrant functional connectivity between the sensory cortex and the frontal cortex in a group of migraine patients compared to a healthy control group [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has repeatedly been demonstrated how the migraine brain differs morphologically from the healthy brain in several brain regions. Moreover, these alterations appear to progress over time and with attack frequency [25,28,[31][32][33][34][35]. However, there may well be alterations at the level of structural synaptic plasticity that cannot be detected in vivo in humans with available methods.…”
Section: Discussionmentioning
confidence: 99%
“…Results from these investigations have identified differences between control and migraine brains with regard to resting state activity and structure of gray and white matter. Differences have been detected in the frontal lobes, corpus callosum, the limbic system, cerebellum, the brainstem and nociceptive regions, although findings are not consistent across studies [22,24,25,[27][28][29][30][31][32][33][34][35][36]. In addition to regional differences, cortical thickness has been reported to differ between migraine patients and controls, and even correlate to attack frequency [37].…”
Section: Introductionmentioning
confidence: 94%